2011
DOI: 10.1158/0008-5472.can-11-1466
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Induces Intratumoral Expression of Chemokines in Cutaneous Melanoma, Favoring T-cell Infiltration and Tumor Control

Abstract: T-cell infiltration is known to impact tumor growth and is associated with cancer patient survival. However, the molecular cues that favor T-cell infiltration remain largely undefined. Here, using a genetically engineered mouse model of melanoma, we show that CXCR3 ligands and CCL5 synergize to attract effector T cells into cutaneous metastases, and their expression inhibits tumor growth. Treatment of tumor-bearing mice with chemotherapy induced intratumoral expression of these chemokines and favored T-cell in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
176
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(187 citation statements)
references
References 37 publications
9
176
0
2
Order By: Relevance
“…In accord with the recent study by Downs-Canner et al (27), we also showed upregulation of the CCR5 ligand, CCL5 (RANTES) at the protein level, along with a slight, but not significant, increase in the Th2 cytokine IL-10. Increased CCL5 levels have been associated with unfavorable outcomes in some cancers (35), but they predict survival in others (36), regulating antitumor immunity (37) and synergizing with CXCR3 ligands to attract effector T cells into cutaneous metastases and inhibit tumor growth (38). Interestingly, we found a reduction in plasma G-CSF levels in C3aR-deficient mice, a result in line with previous studies showing an inverse correlation between G-CSF and neutrophil counts, and possibly due to negative feedback mechanisms at the transcriptional level (39).…”
Section: Discussionmentioning
confidence: 99%
“…In accord with the recent study by Downs-Canner et al (27), we also showed upregulation of the CCR5 ligand, CCL5 (RANTES) at the protein level, along with a slight, but not significant, increase in the Th2 cytokine IL-10. Increased CCL5 levels have been associated with unfavorable outcomes in some cancers (35), but they predict survival in others (36), regulating antitumor immunity (37) and synergizing with CXCR3 ligands to attract effector T cells into cutaneous metastases and inhibit tumor growth (38). Interestingly, we found a reduction in plasma G-CSF levels in C3aR-deficient mice, a result in line with previous studies showing an inverse correlation between G-CSF and neutrophil counts, and possibly due to negative feedback mechanisms at the transcriptional level (39).…”
Section: Discussionmentioning
confidence: 99%
“…These strategies rely on naturally existing homing receptors and ligands, and they are powerful because they tap into cells' native migration axes. However, many homing ligands are present in multiple locations throughout the body, the expression of these ligands may vary in time throughout the natural course of disease or in response to therapy, many ligands (such as chemokines) interact with multiple receptors and vice versa, and native receptors for natural ligands can sometimes be found not only on therapeutic cell types but also on cell types that are detrimental for therapy (47,(49)(50)(51)(52). In contrast, the work we have demonstrated here benefits from the use of an orthogonal receptor-drug pair.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of T cells, macrophages in RET mice also displayed reduced ability to support tumor growth (Lengagne et al, 2011). In our own laboratory, we have further observed that the microenvironment of RETAAD cutaneous tumors supports only limited infiltration of CD4 + and CD8 + T cells compared with transplanted B16 tumors (Hong et al, 2011).…”
Section: Melanoma and The Immune Systemmentioning
confidence: 71%